2017
DOI: 10.1038/s41598-017-03615-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced preference for social rewards in a novel tablet based task in young children with Autism Spectrum Disorders

Abstract: Atypical responsivity to social rewards has been observed in young children with or at risk of Autism Spectrum Disorders (ASD). These observations contributed to the hypothesis of reduced social motivation in ASD. In the current study we develop a novel task to test social reward preference using a tablet computer (iPad), where two differently coloured buttons were associated with a social and a nonsocial rewarding image respectively. 63 young children, aged 14–68 months, with and without a diagnosis of ASD to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 56 publications
(40 reference statements)
6
41
0
Order By: Relevance
“…The results from the button task are consistent with the original report by Ruta and colleagues [23], where typically developing children did not show an overall social preference. Even though the button task is a simpler version of the instrumental tasks used previously, it still requires participants to remember the association between the cue (button) and reward (linked videos).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results from the button task are consistent with the original report by Ruta and colleagues [23], where typically developing children did not show an overall social preference. Even though the button task is a simpler version of the instrumental tasks used previously, it still requires participants to remember the association between the cue (button) and reward (linked videos).…”
Section: Discussionsupporting
confidence: 90%
“…Unlike preferential looking measures, behavioural approach or instrumental choice tasks have been less consistent in indicating preference for social stimuli in neurotypical children [20][21][22][23]. In the present study, we replicated the findings by Ruta and colleagues [23] using an adapted version of the original task. Children showed no significant preference for social stimuli on the button task.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Those diagnosed with ASD have early deficits in social cognition that are thought to reduce social interest and motivation, leading to the theory that because those with ASD do not find social interactions rewarding, they are not motivated to seek them out (Novacek, Gooding, & Pflum, ). Several recent studies have found support for the social motivation theory including a preference of ASD individuals for nonsocial over social videos (Dubey, Ropar, & Hamilton, ), a reduced preference for social stimuli in toddlers diagnosed with ASD (Ruta et al., ), and an inverse relationship between ASD traits and self‐reported pleasure from social interactions (Novacek et al., ).…”
Section: Introductionmentioning
confidence: 99%